Identity and Distribution of 'Magar' Bamboo Dendrocalamus somdevai in Western Idmalaya - Naithani, H. B.; Pal, Mohinder (Indian Forester, 2001)
During Bamboo survey a species viz. Dendrocalamus hamiltonii distributed in Western Himalaya called 'Magar' in Himachal Pradesh was critically examined and found distinct from Dendrocalamus hamiltonii. It belongs to Dendrocalamus somdevai a species recently been described from Uttaranchal. This indicates that Dendrocalamus hamiltonii is distributed in Eastern India, Andhra Pradesh. Nepal, Bangladesh, Myanmar, China and Vietnam. Dendrocalamus somdevai provides excellent fodder in winter. Its germplasm is available in the University of Palampur, Himachal Pradesh.